Revitalisasi Peran Muhammadiyah Dalam Bidang Politik, Ekonomi Dan Pemberdayaan Perempuan - fitriany sari; Faryanita Faryanita; M. Amin (CV. ITTC INDONESIA, 2026)
Muhammadiyah is one of the largest Islamic organizations in Indonesia, founded on November 18, 1912, by KH. Ahmad Dahlan. Since its establishment, Muhammadiyah has not only focused on religious activities but has also actively contributed to national politics, economic development, and women’s empowerment. This study aims to analyze and revitalize the role of Muhammadiyah in these three sectors. The research employs a qualitative approach using library research based on theoretical sources and organizational data. The findings indicate that in the political field, Muhammadiyah promotes the concept of high politics or value-based politics by maintaining institutional neutrality from practical party politics while remaining active in national affairs. In the economic sector, Muhammadiyah develops charitable enterprises, cooperatives, and community economic empowerment through structural, functional, and cultural approaches. Meanwhile, in women’s empowerment, Muhammadiyah through its autonomous organizations such as Aisyiyah and Nasyiatul Aisyiyah has significantly contributed in education, health, and women’s economic development. The revitalization of these roles is essential to strengthen Muhammadiyah’s contribution in building a progressive Islamic society.